Estudo morfoambiental dos relevos vulcânicos da região metropolitana de Fortaleza, CE. - Costa, Anatarino Torres da (2008)
The Metropolitan Area of Fortaleza, capital of the Ceará State, North-east Brazil, is composed by a diversified geomorphologic landscape, which has been structured and modified during geological times. Among this diversity, there are forms originated by the last volcanic event occurred in the Brazilian northeast, 30 millions ago, which create a very singular local morphology. Such prominences were probably originated by the action of a ‘hot spot’. The magma extrusion resulting of this action created a geological domain named « Formation Messejana ». This formation is composed by a set of ten volcanic reliefs, as small prominences disposed in many sectors of the city of Fortaleza coastal area and adjacencies. Among these prominences are the Caruru, Ancuri and Pão de Açucar hills. The present research has as objective to establish the origin, the processes of morphological structuration, the morphological characterization and the environmental situation of these volcanic prominences, as well as define the phases of morphological evolution of the local landscape. For this purpose, the following stages have been developed: bibliographical research about the matter, interpretation of cartographical data, with the use of diverse scales and thematic maps and cartographical geoprocessing techniques, and field work. As results, we are able to conclude that the three prominences of the Formation Messejana analyzed in this work present form of dome-like necks (Caruru and Pão de Açucar) and ellipsoidal form (Ancuri), being composed by alkaline rocks. Such prominences are characterized for presenting different extensions and altitudes, steep slopes, poorly developed soils and sparse vegetation cover. In the present moment, the Caruru hill is a place of mining activity, being partially destroyed due to the extraction of the rocks for the civil construction. This situation creates environmental problems, which may be extended to other volcanic hills, fact that put in danger of eradication these singular elements of the Ceará geomorphic landscape.